Tahap Integrasi Kaum Di Kalangan Pelajar Kolej Universiti Sains dan Teknologi Malaysia (Jurnal Pembangunan Sosial, 2009)
This study presents analyses of data from Penyelidikan Tahap Integrasi Kaum di Kalangan Pelajar Kolej Universiti Sains dan Teknologi Malaysia conducted in 2005 to measure the level of etnic integration among students. A total of 258 students were choosen as respondents. Results indicate that the level of etnic integration among students in KUSTEM is high. This finding concludes that university which poses a small number of students may results in high level of etnic integration.